Factors Influencing the Enrolment Intention among International Students in Private Higher Educational Institution (HEI) In Malaysia - Kazi, Rezwana Alam (2014)
This researcher’s aim is to identify the factors that influencing the enrolment intention among international students in private Higher Education Institutions (HEIs) in Malaysia. More specifically, it is to consider the combined effect of location, cost, service quality and reputation of the institution. Malaysia has now become an educational hub. During the last few years, more and more international students are considering Malaysia to be their ideal place for higher education. There is no doubt that there are some factors attracting international students to Malaysia for higher studies. The main purpose of this study is to identify significant factors that influence international students in their choice. The significance of this research study is to better understand students’ demands and allow opportunities for institutions to adopt new marketing strategies to attract more international students. This research uses the descriptive research design and a primary method of data collection. To complete this study the author applied the convenience sampling method. SPSS was used to analyze descriptive and significant level of dependent variable and independent variables.